Ways to Improve the Ecological Safety of the Livestock Sector under Associative Mycotoxicoses - SEMENENKO, Marina P.; KUZMINOVA, Elena V.; TYAPKINA, Evgenia V.; FOMIN, Oleg A.; RODIN, Igor A. (Journal of Environmental Management and Tourism, 2018)
The problem of accumulation in the animal feed of a large number of mold fungi and their metabolites - mycotoxins - has become very important in recent years. As an effective method of detoxification therapy, enterosorption is proposed to be used with the help of natural aluminosilicate minerals and preparations based on them, which possess sorption, antitoxic, hepatoprotective and antioxidant properties. Using an analog method, four groups of calves were formed, taking into account age and body weight. Intergroup differences consisted of the prescribed medicinal preparations, which were added to the diet of the main ration at a dose of 0,3 g / kg of body weight for 21 days. It has been experimentally proved that preparations on the background of feed of calves, that were fed with mycotoxins and spores of fungi, have a pronounced preventive effect in associative mycotoxicoses. Normalization of metabolic processes in the liver was noted, which was manifested by an increase in the level of total protein in the experimental groups by 24,4%, 18,1% and 19,4%. The level of alanine aminotransferase decreased by 15,2%, 12,3% and 11,3%, tha level of aspartate aminotransferase decreased by 24,2%, 20,9% and 18,7%. At the same time, preparations helped to reduce the endogenous intoxication of the calves' organism and reduce the accumulation in the blood of middle-mass molecules (MMM) by 36,6%, 22,3% and 21,3%.